Women and Pregnancies as an Immediate Target against the Obesity Epidemic (Global Journal of Medical Research, 2021)
The author wishes to enlarge an important current debate among obstetricians trying to sensitize specialists of obesity/endocrinology/nutrition, and make them aware of a possible very important debate: having a "normal shaped" baby (neither too small, nor too big, 10% of SGA, small for gestational age and 10% of LGA, large for gestational age), is possible by an optimal gestational weight gain (optGWG) during pregnancy. This is a simple mathematical linear equation, y= ax+b (y being optimal gestational weight gain, optGWG, x being pre-pregnancy body mass index, ppBMI). Beginning with severe obesity (36 kg/m²), women should not gain weight during their pregnancy, while they should lose weight in higher BMIs (e.g. losing 6 kg for a 40 kg/m² morbid obese). This is predictable since the first trimester of pregnancy.
Keywords: preeclampsia; gestational diabetes; obesity; epidemiology; gestational weight gain; caesarean sections